The Self Reliance Strategy and Refugee Livelihoods: Evidence from Oruchinga Refugee Settlement, South Western Uganda - FRANK, AHIMBISIBWE (International Journal of Research In Social Sciences, 2014)
The self-reliance strategy in Uganda has very good aims of empowering refugees become self -reliant and reduce on their dependence on humanitarian agencies among other reasons. By focusing on Oruchinga refugee settlement, the study found out that, refugees have been able to engage in a number of livelihood strategies both agricultural and non-agricultural in a bid to stand on their own feet. A number of enabling factors ranging from availability of land, labour to favorable weather conditions and local markets have to a small extent favored them to become self -reliant. However, to a big extent refugees are affected by a number of challenges that have made it hard for them to be self-reliant, a reason why they are still dependent on humanitarian agencies for livelihoods support
Keywords: Self Reliance; Strategy; Refugees; Livelihoods; Oruchinga; Refugee Settlement; Uganda